Projected Strengthening of Water Constraint on Seasonal Peak Photosynthesis Under Climatic Warming in Northern Ecosystems - Xingan Chen; Yuefei Huang; Shuo Zhang; Yuting Yang; Shen Tan; Chong Nie; Guangqian Wang; Zhichao Chen (Geophysical Research Letters)
Abstract The seasonal peak of vegetation photosynthesis is a key indicator of terrestrial ecosystem productivity. Water availability and temperature are the primary factors limiting vegetation photosynthesis. In this study, we used solar‐induced chlorophyll fluorescence as a proxy for photosynthesis to investigate water and temperature constraints on peak vegetation photosynthesis across northern ecosystems (north of 30°N). We observed a marked expansion of water‐constrained zones in northern ecosystems over the past two decades. We identified a general relationship between mean annual temperature and precipitation that effectively distinguishes between temperature‐ and water‐constrained ecosystems. This relationship enabled us to project future shifts in these constraints under different climate change scenarios. Our results indicate that water‐constrained regions are projected to expand from 31% to 40%, excluding no‐data areas, under the moderate climate scenario (SSP245) and to 53% under the high‐emissions scenario (SSP585) by 2100, with complementary shrinkage of temperature‐constrained regions.